Mobile System For Student Attendance In School (MS-SAS) - Ajal, Elmehdi A. Abulghasem (2008)
Mobile technology enables people to access digital information located in the Internet or also beyond the reach of stationary Internet access. The focus of this project is to apply Mobile-application field, particularly in observing students' attendance in schools by instructors and parents of the students, the prospective system will facilitate to teachers to make attendance in the class and save it in the database of the school, the head also can add student, and the all of them parents, teachers and head of school can oversee their students during school hours. To achieve this goal, the study will adopt Object oriented development life cycle as a methodology, the four phases will be discussed in section of Research Methodology. Usability testing will be conducted to examine user's satisfaction, lastly to document the models of prototype.